Monetary Policy and Asset Mispricing - Benjamin Beckers; Kerstin Bernoth (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper investigates whether conventional interest rate policy of central banks is a suitable instrument to attenuate excessive mispricing in stocks as suggested by the proponents of a "leaning against the wind" (LATW) monetary policy. For this, we decompose the stock price into a fundamental, a risk premium and a mispricing component. We argue that mispricing can arise for two reasons: (i) from false subjective expectations of investors about future fundamentals and equity premia, and (ii) from the inherent indeterminacy in asset pricing in line with rational bubbles. Employing a partial equilibrium asset pricing model, we show that the response of the excessive stock price component to a monetary policy shock is ambiguous in both the short- and long-run, and depends on the nature of the mispricing. Subsequently, we evaluate the scope for a LATW policy empirically by employing a time-varying parameter VAR with a flexible identification scheme based on impact and long-run restrictions using data for the S&P500 index from 1962Q1 to 2014Q4. We find that a contractionary monetary policy shock in fact lowers stock prices beyond what is implied by the response of their underlying fundamentals.
Keywords: E44; E52; G12; 330